2015
DOI: 10.1039/c5ra14093e
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidative cleavage of terminal olefins into aldehydes catalyzed by copper(ii) complex

Abstract: ARTICLE This journal isA simple method for oxidative C=C bond cleavage of terminal olefins to aldehydes with H 2 O 2 catalyzed by copper(II) complex LCu consisted of copper(II) and macrocyclic ligand 5,7,12,14-tetramethyl-1,4,8,11-tetraazacyclotetradeca-4,7,11,14-tetraene (L) was described. This study indicated that the copper(II) complex displayed excellent catalytic ability for the selective oxidation of terminal olefins to aldehydes with high selectivity (S>90%) in CH 3 CN at 30 ℃ . The possible catalytic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 55 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Indeed, no conversion of the terminal alkene in the cardanol triene was observed. Hence, this photooxygenation may be applied as orthogonal method to oxidations that specifically convert terminal double bonds [30,31] . Then, the CNSL mixture was subjected to the standard flow photo‐oxygenation conditions with a residence time of 10 min (Figure 2, top).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, no conversion of the terminal alkene in the cardanol triene was observed. Hence, this photooxygenation may be applied as orthogonal method to oxidations that specifically convert terminal double bonds [30,31] . Then, the CNSL mixture was subjected to the standard flow photo‐oxygenation conditions with a residence time of 10 min (Figure 2, top).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, this photooxygenation may be applied as orthogonal method to oxidations that specifically convert terminal double bonds. [ 30 , 31 ] Then, the CNSL mixture was subjected to the standard flow photo‐oxygenation conditions with a residence time of 10 min (Figure 2 , top). The evolution of the peroxy functions was determined by downstream reduction with PPh 3 and quantification of the amount of formed triphenylphosphine oxide, OPPh 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Heretofore, various metal- and non-metal-based methods such as the Lemieux–Johnson protocol (OsO 4 /NaIO 4 system), transition metals (Ru, Pd, Re, Fe, Au, Mn, Mo, W) in the presence of oxidizing reagents, m -chloroperoxybenzoic acid ( m -CPBA), pyridinium chlorochromate (PCC), N -hydroxyphthalimide (NHPI), 2,2-azobis­(isobutyronitrile) (AIBN), and photochemical methods have been applied as the oxidative cleavage systems. However, despite tremendous attempts made in this field, these methods still have many disadvantages. In other words, using toxic, expensive, nonrenewable metal resources, toxic organic solvents, large amounts of oxidants, harsh conditions, producing excessive byproducts, low selectivity, and the need for PTC along with limited substrates are the features of the current cleavage systems. Very recently, selenium-containing compounds as a nonmetal catalyst are reported as active and sustainable catalysts for the oxidative reaction in the presence of green oxidants. In this regard, Yu and co-workers synthesized polyselenides from the reaction of dihalohydrocarbons with NaHSe as a homogeneous oxidative cracking catalyst of alkenes in the presence of excess amount of H 2 O 2 as an oxidant .…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic aldehydes, high-value aromatic compounds containing carbonyl groups, are widely used in the food, perfume, pharmaceuticals, and chemical industries. Nowadays, the limited supply and high price of the extract of spiceberry and environmental pollution caused by chemical synthesis have made researchers considering to develop a green and economical method for the synthesis of aromatic aldehydes. ,, Phenylpropanoid acids, natural secondary metabolites, are often released from the biomass of lignin, such as sugar beet pectin, coffee pulp, tobacco plants, and polysaccharides of graminaceous plants. Significantly, phenylpropanoid acids could provide excellent carbon skeletons for synthesizing a wider range of highly value-added aromatic compounds. , Researchers have confirmed that phenylpropanoid acids could be transformed into aromatic aldehydes in the past 10 years. , Ferulic acid (FA), caffeic acid (CA), 4-hydroxycinnamic acid (HA), and cinnamic acid (CIA), which belong to natural phenylpropanoid acids with phenyl propylene units, are excellent precursors for aromatic aldehyde biosynthesis. , In addition, aromatic aldehydes produced from natural phenylpropanoid acids by biosynthesis are considered as a “flavoring agent” by the US and European legislation (Flavoring Regulation (EC) No. 1334/2008) .…”
Section: Introductionmentioning
confidence: 99%